2011
DOI: 10.1007/s11273-011-9240-4
|View full text |Cite
|
Sign up to set email alerts
|

Great Lakes coastal wetland habitat use by seven turtle species: influences of wetland type, vegetation, and abiotic conditions

Abstract: Great Lakes coastal wetlands are important habitats for turtles but few studies have looked at factors driving community structure in these systems. We evaluated the effects of wetland type, vegetation, and abiotic conditions on turtle communities for 56 wetlands in Lakes Huron, Michigan, and Superior with data collected during the summers of 2000-2008. Overall, 1,366 turtles representing seven species were captured using fyke nets. For the majority of species, catches were highest in drowned river mouth wetla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…), water lily (Nuphar advena and Nymphaea odorata), common reed (Phragmites australus), and various species of submerged aquatic vegetation (Albert 2003). These characteristics make Lake Michigan drowned river mouth wetlands ideal habitat for a number of turtle species (Wieten et al 2012).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…), water lily (Nuphar advena and Nymphaea odorata), common reed (Phragmites australus), and various species of submerged aquatic vegetation (Albert 2003). These characteristics make Lake Michigan drowned river mouth wetlands ideal habitat for a number of turtle species (Wieten et al 2012).…”
Section: Methodsmentioning
confidence: 99%
“…For example, marine turtles accumulate cadmium primarily via their diet (Caurant et al 1999). Since freshwater turtles feed at multiple trophic levels (Georges 1982) and often inhabit degraded aquatic ecosystems (Wieten et al 2012), they are at particular risk for heavy metal contamination. Relative to other macrofauna such as fish and waterfowl, turtles remain an infrequently studied component of Lake Michigan coastal ecosystems, especially with regard to heavy metal contamination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Wisconsin, hundreds of map turtles were often collected per day in gill nets set for carp (Vogt 1980). Map turtles are also occasionally captured in fyke nets used in commercial fisheries (Carrière et al 2006;Gislason et al 2010;Larocque et al 2012a;Wieten et al 2012;Midwood et al 2015). Carrière et al (2006) found 16 dead G. geographica in commercial fishing fyke nets in the St. Lawrence River in a single week.…”
Section: 8mentioning
confidence: 99%
“…However, for most turtles this is poorly known. Freshwater turtles are particularly vulnerable to habitat fragmentation, as they not only depend on the aquatic environment, but also need the terrestrial environment for nesting, basking, dispersal and hibernation (Marchand and Litvaitis 2004;Ryan et al 2008;Wieten et al 2012;Hill and Vodopich 2013;Ryan et al 2014;Hamer et al 2018).…”
Section: Introductionmentioning
confidence: 99%